Numerical Simulation of the Effects of Biodiesel Fuel Use on the Performance of the SWD 9TM 410 Engine - Rendri Julian Restiawan; Muhammad Agung Bramantya; Willie Prasidha (Jurnal Locus Penelitian dan Pengabdian, 2026)
The use of B40 Biodiesel as the main fuel in the Diesel Power Plant (PLTD) within PT PLN Nusantara Power UP Kapuas reflects the government's policy to reduce fuel oil imports and support the energy transition to renewable sources. In the SWD 9TM 410 engine at ULPLTG/D Siantan, the use of B40 Biodiesel provides significant changes to combustion characteristics, engine performance, and exhaust emissions. This study aims to model and analyze the combustion process of B40 Biodiesel using the Computational Fluid Dynamics (CFD) method through ANSYS Forte software with a multicomponent chemical mechanism approach. Simulation was carried out in the combustion chamber domain of cylinder 1 based on the actual geometry of the engine with output parameters in the form of peak pressure (Pmax), ignition delay (ID), rate of heat release (RoHR), indicated horsepower (IHP), temperature distribution, and formation of NOx and CO2 emissions. Validation was carried out using experimental data from engine operation tests. The simulation results show that the variation of the biodiesel mixture has an influence on combustion characteristics, engine performance, and the formation of exhaust gas emissions. B100 exhibited a 6.4% lower power output than B0 due to its lower heating value. In addition, differences in fuel characteristics result in variations in maximum cylinder pressure values, heat release rates, combustion temperatures, and NOx and CO2 emission concentrations at each loading level. Under the simulated conditions, the increase in the biodiesel fraction showed a tendency to produce lower combustion temperatures and NOx emissions than B0. The findings show that the fuel composition plays an important role in determining the combustion and emission characteristics of the SWD 9TM 410 diesel engine.